A randomized trial to assess the acceleration of viral clearance by the combination Favipiravir/Ivermectin/Niclosamide in mild-to-moderate COVID-19 adult patients (FINCOV) - Taweegrit Siripongboonsitti; Kriangkrai Tawinprai; Panisadee Avirutnan; Kunlakanya Jitobaom; Prasert Auewarakul (Elsevier, 2024)
Background: The efficacy of the viral clearance and clinical outcomes of favipiravir (FPV) in outpatients being treated for coronavirus disease 2019 (COVID-19) is unclear. Ivermectin (IVM), niclosamide (NCL), and FPV demonstrated synergistic effects in vitro for exceed 78% inhibiting severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) replication. Methods: A phase 2, open-label, 1:1, randomized, controlled trial was conducted on Thai patients with mild-to-moderate COVID-19 who received either combination FPV/IVM/NCL therapy or FPV alone to assess the rate of viral clearance among individuals with mild-to-moderate COVID-19. Results: Sixty non-high-risk comorbid patients with mild-to-moderate COVID-19 were randomized; 30 received FPV/IVM/NCL, and 30 received FPV alone. Mixed-effects multiple linear regression analysis of the cycle threshold value from SARS-CoV-2 PCR demonstrated no statistically significant differences in viral clearance rates between the combined FPV/IVM/NCL therapy group and the FPV-alone group. World Health Organization Clinical Progression scores and symptomatic improvement did not differ between arms on days 3, 6, and 10, and no adverse events were reported. No patients required hospitalization, intensive care unit admission, or supplemental oxygen or died within 28 days. C-reactive protein on day 3 was lower in the FPV/IVM/NCL group. Conclusion: Viral clearance rates did not differ significantly between the FPV/IVM/NCL combination therapy and FPV-alone groups of individuals with mild-to-moderate COVID-19, although the combined regimen demonstrated a synergistic effect in vitro. No discernible clinical benefit was observed. Further research is required to explore the potential benefits of FVP beyond its antiviral effects.Trial registration: TCTR20230403007, Registered 3 April 2023 - Retrospectively registered, https://trialsearch.who.int/Trial2.aspx?TrialID=TCTR20230403007